Microstrip antenna with complementary split ring resonator loaded ground plane for gain enhancement. Issue 2 (February 2015) - Pandeeswari, R.; Raghavan, S.
ABSTRACT In this article, microstrip patch antenna with complementary split ring resonator (CSRR) loaded ground plane is proposed for gain improvement. Gain was improved by introducing CSRR slots on the ground plane. The proposed antenna is designed, fabricated, and tested. Measured results are in good agreement with simulation results. The proposed antenna has a size of 40 × 46 × 1.6 mm3. The measured impedance bandwidth is 100 MHz (return loss <−10 dB) from 2.4 to 2.5 GHz, which covers instruments, scientific and measurement (ISM) band applications. Omnidirectional radiation pattern obtained in H‐plane and bidirectional radiation pattern obtained in E‐plane. Parametric study of CSRR was done to obtain best results. The proposed antenna is simple, has good radiation pattern, and very good gain of 5.93 dBi at resonant frequency. Size reduction of 10% was also achieved and bandwidth is slightly greater than unloaded antenna. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:292–296, 2015